Evolution of glioma exosome research: emerging trends and global collaborations (2005–2025) - Yijun Zeng; Ting Liu; Shixue Jing; Yongfeng Wang; Jihong He; Hui Cao; Xinlian Liu; Lushun Zhang (Discover Oncology)
Abstract Background Glioma, a tumor derived from neuroglial cells of the central nervous system, is characterized by its high malignancy, frequent recurrence, and high mortality rate. Recent advances in exosome research related to gliomas have propelled this emerging field as a pivotal area of clinical neuroscience investigation. Despite extensive focus on glioma exosome research, a systematic visual analysis of this field remains lacking. Using bibliometric analysis, this study maps the scientific landscape of glioma exosome research to identify current hotspots and emerging trends in neuro-oncology. Methods This bibliometric analysis extracted glioma exosome publications from the Web of Science Core Collection(WoSCC) spanning 2005–2025. Following systematic screening, 209 articles constituted the analytic corpus. Using VOSviewer(VOS), Scimago Graphica, and CiteSpace, we mapped contributions across geographic, institutional, authorship, and conceptual domains. This visualization delineates the field’s intellectual structure, identifies current research foci, and projects emerging trends in neuro-oncology. Results Annual publication volume on glioma exosomes has increased significantly since 2019. China and the United States are the predominant contributors, collectively driving field advancement. Leading institutions include Shandong University, Shandong Provincial Key Laboratory of Brain Function Reconstruction, and Capital Medical University, whose productivity metrics reflect substantial influence. Notably, Chinese institutions comprise 90% of the top 10 productive entities. Key investigators Li Gang and Xue Hao demonstrate exceptional scholarly output, advancing the field through high-impact research. NEURO-ONCOLOGY emerges as the premier journal, evidenced by its dominant citation frequency. Thematic analysis reveals three conceptual domains: Exosome biogenesis in gliomas, Glioblastoma extracellular vesicle signatures, and Exosome mediated drug delivery systems-representing current priorities and evolving research frontiers. Conclusion Exosomes have attracted considerable attention in glioma research, establishing themselves as a cutting edge thematic focus. This study applies bibliometric rigor to map research trajectories and conceptual evolution in glioma exosomes. The analysis establishes foundational frameworks that prioritize future investigation domains while objectively quantifying the field’s translational potential. These evidence-based insights will accelerate mechanistic discovery and clinical translation in neuro-oncology.